The relationship between pop music and lyrics: A computerized content analysis of the United Kingdom's weekly top five singles, 1999–2013. (July 2021) - North, Adrian C; Krause, Amanda E; Ritchie, David
The majority of research on music aesthetics treats music and lyrics as discrete entities, despite the artistic imperative that they should relate to one another in some way. This research computer analyzed both the music and lyrics of the songs to have reached the weekly UK top five singles chart from January 1999 to December 2013 ( N  = 1, 414). The findings indicate that the typicality of a given set of lyrics relative to the corpus as a whole was associated with their popularity; that there were numerous associations between each of six mood scores assigned to the music and various aspects of the lyrics (e.g., passionate music was associated with lyrics addressing hardship and less concern with precise numerical terms); and that the relative contribution of the lyrics and music to overall popularity varied according to the means by which these were operationalized so that, for instance, music and lyrics contributed equally to explaining peak chart position, whereas music outperformed lyrics in explaining the number of weeks spent on the top five. Pop music and its lyrics are related to one another, and the relationship can be explained to some extent via existing concepts in the aesthetics literature.